Altered Spontaneous Brain Activity in Patients With Idiopathic Trigeminal Neuralgia: A Resting-state Functional MRI Study. Issue 7 (July 2018) - Yuan, Jie; Cao, Song; Huang, Yue; Zhang, Yi; Xie, Peng; Zhang, Yu; Fu, Bao; Zhang, Tijiang; Song, Ganjun; Yu, Tian; Zhang, Mazhong
Abstract : Objectives: To identify the changes of local coherence and intrinsic brain activity in resting-state idiopathic trigeminal neuralgia (ITN) patients by using regional homogeneity (ReHo) and fractional aptitude of low-frequency fluctuation (fALFF) analysis. Methods: ReHo and fALFF were analyzed in 23 ITN patients and 23 age-matched and sex-matched pain-free controls to detect the functional abnormality in the brains of ITN patients. Correlations between ReHo and fALFF were analyses. ITN pain intensity were also assessed in the ITN group. Results: Compared with pain-free controls, ITN patients exhibited significantly abnormal ReHo and fALFF in several brain regions, including the cerebellum, cingulate cortex, temporal lobe, putamen, occipital lobe, limbic lobe, precuneus, insula, medial, and superior frontal gyrus compared with healthy controls. Correlation analysis showed that ReHo values of several altered brain areas positively correlated with visual analog scale values. But no correlation was found between fALFF and visual analog scale. Discussion: Our results showed that ITN patients exhibited significantly abnormal spontaneous brain activity in several brain regions that are involved in pain modulation and perception. The present study reflects the maladaptive process of daily pain attacks and may enhance the understanding of how chronic pain affects local intrinsic brain activity.